Numerical and Experimental Analyses of Vibrations of Annular Plates with Multiple Eccentric Holes - Noga, S. (Проблемы прочности, 2016)
This paper deals with the free transverse vibrations of annular plates with geometrical discontinuities in form of eccentric holes and rims. The finite element method and experimental studies are used. Solid and shell finite element models are employed in the numerical analysis using the commercial ANSYS software. The calculated results are verified by the original experimental data via innovative laser measurement techniques. Numerical and experimental results of this study adequately describe the phenomenon of dividing natural frequency values corresponding to the mode shapes, where the number of nodal diameters is a factor of the number of through holes. The proposed procedure of analysis of transverse vibrations of annular plates with eccentric through holes arranged over the specified radius is recommended for engineering applications.